KIDNEY HEALTH EDUCATION AND URINE CREATININE TESTING FOR MOTHERS IN SENDANGMULYO TEMBALANG, SEMARANG - Roni Afriansya; Ririh Jatmi Wikandari; Ichsan Hadipranoto; Iin Desmiany Duri; Widodo; Sy Didik Widiyanto; Hamun Mirza Ababil; Niska Ramadani (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
The background of this activity is the high incidence of kidney failure in Indonesia and the low utilization of simple screening in the community. The service was carried out in Sendangmulyo Village, Tembalang, Semarang, targeting mothers as family health managers. The purpose of this activity was to improve kidney health literacy and provide feedback through urine creatinine testing. The approach used was a pretest-posttest, which was measured before and after education. The intervention took the form of counseling using leaflets and brief discussions. 24-hour urine samples were collected using containers accompanied by instructions during distribution. Creatinine was tested using test strips. Thirty mothers participated in the activity, which went according to plan. Knowledge scores increased among all participants. All urine creatinine results were within the reference range, indicating no filtration disorders. These findings suggest that concise and contextual education effectively improves literacy, and that simple creatinine screening can be implemented at the community level. This program is relevant for strengthening kidney disease prevention in households and can serve as an entry point for ongoing monitoring in further services.